Research on multi-domain collaboration based method of TDD large-scale networking - Xiaoyun WANG; Wei DENG; Long ZHANG; Qi SUN (Dianxin kexue)
How to maximize the network service capability under the constraints of massive nodes and multi-domainresources is the core problem faced by TDD large-scale networking.The method of TDD large-scale networking under fully collaborative optimization architecture were innovatively proposed, which could maximize network service capabilities through inter layer and intra layer collaboration among wireless connection layer, signal processing layer and service control layer.Aiming at efficient use of wireless resources, the method of multi-domain conversion in wireless connection layer were put forward, including the principles and mechanism of space-time-frequency-code multi-domain conversion.The results of practical verification in 4G/5G existing network show that the proposed architecture and method of TDD large-scale networking can effectively control the interference while improving utilization of multi-domain resourcesto maximize network capacity.